Origins and Trends of “Jangar” Studies in Mongolia (Mongolian Journal of Arts and Culture, 2025)
This article examines the origins and development of Jangar epic studies in Mongolia through historical comparative analysis, content analysis, and bibliometric methods. Thirty-two paper-based research works by Mongolian scholars were selected and analyzed as primary sources. The research results show that Jangar studies in Mongolia have developed since 1900 across multiple directions including origins, variant comparisons, aesthetics, mythology, customs, magic and divination, and values. Mongolian scholars such as B.Sodnom, Ts.Damdinsüren, U.Zagdsuren, S.Luvsanvandan, G.Nandinbilig, T.Bayasgalan, and S.Dulam have made significant advances in recording and collecting (17 works) and aesthetics, mythology, customs, magic and divination, and values (15 works). Since the 1990s, Mongolian Jangar studies have entered a multidisciplinary and interdisciplinary research phase, introducing new theoretical and methodological approaches including mythology, symbolism, cultural anthropology, and comparative studies. The research confirms that the Jangar epic serves not only as a Mongolian heroic epic but also as a cultural bridge connecting regions where Mongolian ethnic groups reside, playing a crucial role in unifying ethnic identity and cultural heritage.Монгол дахь “Жангар” судлалын тоймХураангуй: Энэхүү өгүүлэлд Монгол дахь “Жангар” судлалын үүсэл, хөгжлийг түүхэн харьцуулалт, контент анализ, библиометрик арга зүйгээр судалсан. Монгол эрдэмтэн судлаачдын 32 цаасан суурьтай судалгааны бүтээлийг эх хэрэглэгдэхүүнээр сонгон авч шинжилсэн. Судалгааны үр дүнгээр Монгол дахь Жангар судлал нь 1900 оноос эхлэн гарал үүсэл, хувилбарын харьцуулалт, гоо зүй, домог зүй, зан үйл, дом шившлэг, үнэт зүйлс зэрэг олон чиглэлээр хөгжиж ирсэн байна. Монгол эрдэмтэд Б.Содном, Ц.Дамдинсүрэн, У.Загдсүрэн, С.Лувсанвандан, С.Дулам, Т.Баясгалан, Г.Нандинбилиг нар туулийн бүртгэл цуглуулга (17 бүтээл), гоо зүй, домог зүй зан үйл, дом шившлэг, үнэт зүйлс (15 бүтээл) зэрэг чиглэлээр судлан сурвалжилсан байна. Монгол дахь Жангар судлал нь 1990-ээд оноос эхлэн домог зүй, бэлгэдэл зүй, соёлын антропологи, харьцуулсан судалгааны шинэ онол арга зүйг нэвтрүүлж, салбар дундын олон талт судалгааны шатанд хөгжиж байна. Жангар тууль нь монгол угсаатан тархсан бүс нутгуудыг холбосон соёлын гүүр, угсаатны танин мэдэхүй, өв уламжлалыг нэгтгэх чухал үүрэг гүйцэтгэж байгаа ажиглагдаж байна.Түлхүүр үгс: Жангар, монгол, судлал, тууль, үүсэл, хөгжил